PERAN SISTEM INFORMASI MANAJEMEN POLITEKNIK SAWUNGGALIH AJI PURWOREJO DALAM RANGKA PENINGKATAN MUTU PELAYANAN - Dian Rukmawati (Politeknik Sawunggalih Aji, 2017)
Polytechnic Sawunggalih Aji Purworejo that also called as POLSA, had faced upon the high rapid of information technology as well. This research aim to portray an application system which was applied in this organization and try to submit some recommendation such a new information system to be applied and developed based in fully computerization. In order POLSA’s academic information system could be operated as good as it was expected by all users in the organization, so it was needed to develop software based on re-engineering. Beside as a private organization POLSA had to placed her position in the right track within it industries, accordingly an application of advance technology was as seemed as a must. The new software model which was analyzed in this research was called RAPID i.e. Rapid Application Development, such a methodology that was able respond in high speed to all users, over wider scopes. This research was going to describe the wide activities and the result they were produced in all stages of development. POLSA’s academic information system would be developed in wide areas completely. Finally such things specially what kind of application which was recently had been run and what things in the future should be applied. Key words : academic information system, re-engineering software